Carcinogenic and mutagenic agents in the workplace, Poland, 2011-2012 - Anna Pałaszewska-Tkacz; Sławomir Czerczak; Katarzyna Konieczko (Nofer Institute of Occupational Medicine, 2015)
Background: The objective of the study was the analysis of structure of carcinogenic or mutagenic chemical substances and dusts occurring in Polish enterprises, 2011-2012, including the number of exposed employees reported to the "Central register of data on exposure to carcinogenic or mutagenic chemical substances, mixtures, agents or technological processes", Nofer Institute of Occupational Medicine, Łódź. In the paper the aims, range and methodology of data collecting by the Central Register are presented. Material and Methods: Qualitative and quantitative analyses of the data on occupational exposure to carcinogenic substances and technological processes reported by employers were carried out. Results: In 2011-2012 approximately 2600 plants reported more than 300 carcinogenic or mutagenic chemical substances annually. The most common occupational chemical carcinogens/mutagens were: benzene, one of the unspecified gasoline, chromium(VI) compounds, asbestos, chromium(VI) trioxide, ethylene oxide and benzo[a]pyrene. The highest number of employees was exposed to particular polycyclic aromatic hydrocarbons (PAHs). Hardwood dust was the major occupational carcinogen listed in the technological processes inventory with approximately 11 000 employees exposed in about 650 enterprises annually. Conclusions: The amended legislation concerning occupational exposure to carcinogens has not significantly influenced the exposure structure in Poland. Nevertheless it permited to determine the actual total number of the occupationally exposed to carcinogens. Med Pr 2015;66(1):29-38